Effect of Alternative Production and Management Environments on Layer Reproduction System Development - Klein, A.N.; Anderson , K.E.; Golden, J.B. (International Journal of Poultry Science, 2013)
Three different production environments were evaluated for their impact on laying hen reproduction by assessing the ovary and oviducts for the presence of physiological variations. The three environments included free-range (FR = 60), cage-free (CF = 55) and battery cage (BC = 50). The ovaries and oviducts from these hens were collected and weighed during necropsy, then stored in a freezer at -20°F for later analysis. The analysis included the oviduct length and the number of Post-Ovulatory Follicles (POFs), atretic follicles, hierarchical follicles (H = 12-40 mm), small yellow follicles (SY = 5-12 mm), large white follicles (LW = 2-5 mm), small white follicles (SW = <2 mm) and tumor numbers if present on each ovary. Free-range hens had significantly heavier oviduct weights, at 19.4 and 13.5% heavier than oviducts of battery cage and cage-free hens, respectively. The free-range hens also exhibited an increased presence of tumors as well as an increased frequency of multiple tumors on the oviducts. Hens housed in the free-range and battery cage environments had increased numbers of LW follicles compared to the cage-free hens. In addition, the free-range hens had a significantly smaller number of SW follicles when compared to the battery cage hens. Contrary to the popular belief that birds raised in free-range or cage-free environments provide healthier production alternatives than conventional battery cages, this study does not suggest that there is a significant physiological impact on the reproductive capacity of hens housed in these different production environments. However, oviduct health appears to be better in the battery cage and cage-free environments.